The English execution narrative, 1200 - 1700 - Royer, Katherine (The body, gender and culture, 2014)
Royer examines the changing ritual of execution across five centuries and discovers a shift both in practice and in the message that was sent to the population at large. She argues that what began as a show of retribution and revenge became a ceremonial portrayal of redemption as the political, religious and cultural landscape of England evolved